NARATIVE REVIEW PEMANFAATAN INTERNET-OF-THINGS UNTUK APLIKASI SEED MONITORING AND MANAGEMENT SYSTEM PADA MEDIA TANAMAN HIDROPONIK DI INDONESIA - Syifaul Fuada; Endah Setyowati; Galuh Inti Aulia; Dwi Wahyu Riani (INFOTECH journal, 2023)
Hydroponic plants develop every time, and until now, many hydroponic plants are managed by the Indonesian people. The steps for producing hydroponic plants are seeding, transplanting, making hydroponic media, providing hydroponic nutrition, conditioning the water pH, and harvesting. One of the important steps to growing good plants is seeding. Therefore, a system connected to the IoT (IoT) is needed; this system acts as the main processor that can send data from sensors to users. This literature review aims to provide awareness about hydroponic plants and help farmers and the general public to more easily monitor hydroponic plants so that all people can easily do hydroponics at home using the IoT. The method used to compile this research is a literature study, searching for relevant scientific articles on the Google Scholar database using several keywords - seeding, hydroponics, IoT, and microcontrollers, with the year of publication 2016-2022. The IoT application for hydroponics provides many benefits, such as easy control for farmers from the sowing stage to irrigation. However, in the production process, the system requires appropriate parameters. The IoT-based hydroponic system facilitates seeding maintenance with the ESP8266 microcontroller, Arduino Uno microcontroller, DHT-22 sensor, PH-4502c, and TDS sensor.